(untitled) (General Practice, 2023)
Introduction. Destroyed lung syndrome is a severe destruction of the pleural parenchyma due to lung infection, mostly caused by tuberculosis. Besides tuberculosis, necrotizing pneumonia may also lead to this disease complication. Pleural empyema is a frequent consequence of the destroyed lung syndrome. Pleural empyema may occur during the COVID- 19 infection and is negatively correlated with a favorable disease outcome. Case report. A male 50 y/o showed up during the oncall shift during the winter COVID-19 wave with a medical report from the Internal medicine clinic. His personal history is significant for his pneumonectomy in 2016. In the past two months, he had been treated for pneumonia and COVID-19 infection with antibiotics and corticosteroid therapy. Due to prolonged malaise and tachycardia his GP referred him to yet another chest X-ray and lab work. The chest X-ray showed pleural effusion, so he was promptly referred to an on-call hospital. The on-call physician, after looking into the hospital reports, consulted an internal medicine doctor and it was decided to refer the patient to a thoracic surgeon. He was hospitalized for pleural empyema and treated with thoracic drainage using the system of active aspiration. A year later, he feels well, and he regained his appetite, and body mass, with occasional leaking from the thoracic fistule. Conclusion. This case report shows a recurrence of pleural empyema in a patient with pneumonectomy due to necrotizing pneumonia and destroyed lung syndrome, complicated by COVID-19 infection. We aimed to draw the atention of GPs to diseases and disease complications that are rarely met in GP practice and are not otherwise treated on the primary healthcare level.